2015
DOI: 10.4103/1735-1995.172980
|View full text |Cite
|
Sign up to set email alerts
|

Roles of osteopontin and matrix metalloproteinase-7 in occurrence, progression, and prognosis of nonsmall cell lung cancer

Abstract: Background:This study detected osteopontin (OPN) and matrix metalloproteinase-7 (MMP-7) expressions to explore the roles of OPN and MMP-7 in the occurrence, progression, and prognosis of nonsmall cell lung cancer (NSCLC).Materials and Methods:A retrospective study was conducted on NSCLC tissues (n = 152; case group) and adjacent nonneoplastic lung parenchyma (adjacent to tumor >5 cm; n = 152; control group) collected from 152 NSCLC patients. The protein expressions of OPN and MMP-7 were detected by immunohisto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Furthermore, MMP-2 localized to the tumors cells along the luminal surface of the cyst wall, suggesting additional roles for MMPs in the development of cysts in VS (41). Our immunofluorescence and cytokine analysis of cyst fluid did not incorporate MMPs; however, osteopontin was upregulated in cyst fluid and CSF and is known to be a substrate of several MMPs, including MMP-2 (42–45). Furthermore, MCP-1 is known to stimulate the expression of multiple MMPs in various cell types, including cancer (46–49).…”
Section: Discussionmentioning
confidence: 80%
“…Furthermore, MMP-2 localized to the tumors cells along the luminal surface of the cyst wall, suggesting additional roles for MMPs in the development of cysts in VS (41). Our immunofluorescence and cytokine analysis of cyst fluid did not incorporate MMPs; however, osteopontin was upregulated in cyst fluid and CSF and is known to be a substrate of several MMPs, including MMP-2 (42–45). Furthermore, MCP-1 is known to stimulate the expression of multiple MMPs in various cell types, including cancer (46–49).…”
Section: Discussionmentioning
confidence: 80%
“…There are conflicting reports regarding the association between osteopontin expression and grading. Marcil et al (2009) and Rud et al (2012) found a positive correlation between given factors, whereas Boldrini et al (2005) and Donati et al (2005) found this correlation negative [ 19 , 25 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Expression patterns of OPN and MMP-3 were overlapped in the stroma during skin incisional wound healing [61] and those of OPN and MMP-7 were overlapped during involution of the postpartum uterus [62] in mice experiments. Higher expressions of OPN and MMP-7 are closely associated with the occurrence, progression, and prognosis of non-small cell lung cancer (NSCLC) [63].…”
Section: Binding Specificities and Functions Of Mmp-cleaved Opnmentioning
confidence: 99%